Pengembangan Sekolah Berbasis Aset pada Sekolah Dasar Negeri Kabupaten Klaten - Nurhidayah Nurhidayah (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2020)
This study discusses the development of asset-based schools in public elementary schools in Klaten district. The background of this research is the decline in the number of state elementary school students in the Delanggu rice-producing region. Apart from being good news about the success of the family planning program for the local government, the declining number of elementary school-age children is a challenge for prospective principals of public elementary schools in Klaten to develop an asset-based school development program. This is because the school is an ecosystem consisting of resources that are organized and systemic. Innovation and breakthroughs are needed for a breakthrough for the leaders of these institutions, including the tasks that must be carried out by prospective elementary school principals together with the school community. The approach used in this study is the ABCD approach. The results of the study show that the ABCD concept is very helpful for prospective school principals to be able to lead their institutions in solving existing learning problems and developing schools through the preparation of effective and efficient RKS.